PENGARUH LATIHAN VARIASI DRIBBLING TERHADAP KETERAMPILAN MENGGIRING BOLA PADA SSB CHEVRON U-13 PEKANBARU - Sugito Sugito; Slamet Slamet; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The problems raised in this study is "The effect of exercise in dribbling variations towards dribbling skills in SSB Chevron U-13 Pekanbaru" so that athletes can appear and play much better in the future and especially after research and find out if there is an increase in dribbling variations in football games to balance the opponent's game and achieve maximum results in the future. The form of this research is (using the only group of pree-test post-test design approach) with the population of football players in SSB Chevron U-13 Pekanbaru 13. The data in this study are all populations of 20 people. The instrument used in this study used the Dribbling Zig-Zag test, which aims to determine The effect of exercise in dribbling variations towards dribbling skills in SSB Chevron U-13 Pekanbaru. After that, the data is processed with statistics to test the normality using the liliefors test at a significant level of 0.05 α. The hypothesis proposed is that there is influence the effect of exercise in dribbling variations towards dribbling skills in SSB Chevron U-13 Pekanbaru. Based on the normal test analysis, data X produces Lcount of 0.1717 and Ltable of 0.285, which means Lcount < Table. While Y-variable produces Lcount equal to 0.1590 and Ltable equals 0.285. This means Lcount < LTable. There are averages based on the analysis of statistical data variable X 16.87 and the average variable Y is 18.10, then the data is normally distributed. Thus, there is the effect of exercise in dribbling variations towards dribbling skills in SSB Chevron U-13 Pekanbaru.Key Words: Practice Dribbling Variations, Dribbling Skills.